1972
DOI: 10.7164/antibiotics.25.219
|View full text |Cite
|
Sign up to set email alerts
|

Biological Aspects of the Interaction Between Gentamicin and Carbenicillin

Abstract: Carbenicillin is capable of inactivating gentamicin in vitro. This effect is time, temperature and medium dependent. In vitro antibacterial tests demonstrate greater than additive activity in some instances and inactivation in others, particularly after prolonged incubation. Inactivation was not observed in vivo in mouse protection tests. Additive or more than additive combined activity in mouse protection tests occurred only infrequently. Intravenous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…vitro (10,13,14,16 The improved in vitro antimicrobial activity of ODMF compared with fortimicin A was also seen in vivo. Both antibiotics protected mice against all of the infections examined, but the amount of antibiotic required was much greater for infections with P. aeruginosa than for the Enterobacteriaceae.…”
Section: Fig 1 Comparative Bactericidal Activity Ofmentioning
confidence: 94%
“…vitro (10,13,14,16 The improved in vitro antimicrobial activity of ODMF compared with fortimicin A was also seen in vivo. Both antibiotics protected mice against all of the infections examined, but the amount of antibiotic required was much greater for infections with P. aeruginosa than for the Enterobacteriaceae.…”
Section: Fig 1 Comparative Bactericidal Activity Ofmentioning
confidence: 94%
“…However, in vitro studies have demonstrated that at high concentrations penicillins such as carbenicillin and ticarcillin can inactivate aminoglycosides (2,5,10,11,13). Evidence suggests that the inactivation mechanism involves the nucleophilic opening of the penicillin beta-lactam ring, which then combines with an amino group of the aminoglycoside, resulting in the formation of a biologically inactive amide (3,16). The rate of in vitro inactivation is dependent upon temperature, time, the composition of the medium, and the concentration of the betalactam (11,13,14,16).…”
mentioning
confidence: 99%
“…Evidence suggests that the inactivation mechanism involves the nucleophilic opening of the penicillin beta-lactam ring, which then combines with an amino group of the aminoglycoside, resulting in the formation of a biologically inactive amide (3,16). The rate of in vitro inactivation is dependent upon temperature, time, the composition of the medium, and the concentration of the betalactam (11,13,14,16). Aminoglycoside inactivation also can occur in vivo when excretion of both drugs is delayed, as in patients with renal insufficiency (5,6,14).…”
mentioning
confidence: 99%
“…It has been reported that gentamicin is biologically and immunologically inactivated by incubation with carbenicillin in vitro (11,18,19). Therefore, experiments were designed to determine whether tobramycin, measured by radioimmunoassay, would decrease in immunoreactivity after incubation with carbenicillin or other antibiotics containing the 18-lactam ring.…”
Section: Resultsmentioning
confidence: 99%